IJCM_243A: Knowledge, attitude, and practice study on rabies and its prevention in Nanded city of Maharashtra - Fahim Saniya Aiman Mohammad Abdul; Inamdar IF; Gattani PL; Gadekar RD; Ammarah Sana; Maidapwad SL (Wolters Kluwer Medknow Publications, 2024)
Background: Rabies is a fatal disease. One of the main obstacles in reducing the prevalence of the disease is the lack of knowledge about animal bite and measures to be taken after it. Objectives: To access the knowledge attitude and practices related to Rabies, animal bite and utilisation of health care services related to animal bite among general population in a Nanded city of Maharashtra. Methodology: A cross sectional study was conducted among the general public aged more than 18 years in Nanded city of Maharashtra. Knowledge, attitude, and practices of people were assessed using a structured questionnaire. Data was analyzed using the Statistical Package of Social Sciences (SPSS) software. Results: Out of 122 people 89.3 % believed that animal bite causes disease. 82.7% believed rabies is fatal. 79.5% believed rabies can be prevented by vaccine. 81.9 % washed their wound with soap and water while 17.2% applied turmeric or lime. Conclusion: Knowledge about Rabies among general public seems to be superficial. Majority of people are still inclined towards traditional practices